THE VECTOR MOTION DYNAMICS OF SYSTEM COMPONENTS FAILURE INTENSITY WITH CONSIDERATION OF ITS COMPONENT RENEWAL - Malynsky, S.; Nalivayko, L. (Academic journal Industrial Machine Building Civil Engineering, 2017)
A system of differential equations describing the motion vector of failure is obtained in the work. It has been taken into account that the component renewal requires some time. Renewal follows the exponential law with renewal densities for each component i h . Keywords: vector, system, matrix, formula, trivial fixed point, element.